Is Having Your Computer Compromised a Personal Assault? The Ethics of Extended Cognition. Issue 4 (21st December 2016) - CARTER, J. ADAM; PALERMOS, S. ORESTIS
ABSTRACT: Philosophy of mind and cognitive science (e.g., Clark and Chalmers1998 ; Clark2010 ; Palermos 2014) have recently become increasingly receptive to the hypothesis of extended cognition, according to which external artifacts such as our laptops and smartphones can—under appropriate circumstances—feature as material realizers of a person's cognitive processes. We argue that, to the extent that the hypothesis of extended cognition is correct, our legal and ethical theorizing and practice must be updated by broadening our conception of personal assault so as to include intentional harm toward gadgets that have been appropriately integrated . We next situate the theoretical case for extended personal assault within the context of some recent ethical and legal cases and close with critical discussion.